Risk-taking and monetary policy - Zheyu Yang (ZBW - Leibniz Information Centre for Economics, 2022)
“Low for long” interest rate and other accommodative monetary policies increase risk-taking and medium- and long term macro-financial vulnerabilities. This paper aims to contribute to understanding how accommodative monetary policy have reshaped the risk perspective among the fixed-income market investors. I study the effects of People's Bank of China's monetary announcements on domestic corporate bond prices. Exploiting information embedded in high-frequency co-movement of financial assets prices and using a Bayesian structural vector autoregression, I deconstructed market surprises around the central bank's announcements on Reserve Requirement Ratios into shocks to investors' beliefs about monetary policy and shocks to the beliefs about non-monetary fundamentals. Using a sample of 16,738 corporate bonds issued by 2,711 non-financial firms between 2010 and 2020, I find the monetary shocks have strong effects on bond pricing and can explain about one-fourth of the price movement around the releases. I further test the hypothesis of risk-taking, i.e., whether the effects differentiate across various credit risk groups. The result shows risky bonds outperform safer bonds following a monetary easing shock, i.e., a significant increase in appetite for risk after monetary policy becomes accommodative. More importantly, the asymmetry between the effects of monetary easing and tightening further confirms the role of accommodative monetary policy as a key driver in risk-taking. The findings raise implications for financial stability and macroprudential policy.
Keywords: C11; E43; E52; G12; 330; risk-taking; monetary policy; asset prices; China economy